2018
DOI: 10.1136/jnnp-2017-317817
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the contribution and strategic distribution patterns of neuroimaging features of small vessel disease in poststroke cognitive impairment

Abstract: Multiple types of SVD neuroimaging features jointly had a significant impact on global and domain cognitive functionings after stroke on top of AILs. The map of strategic cognitive-relevant regions of SVD features may help clinicians to understand their complementary impact on poststroke cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…better than a single acute infarct or SVD marker at 3 to 6 months after ischemic stroke. 10 Similar observations were made in cross-sectional, population-based studies of older adults, in which the concurrence of multiple SVD markers, compared with a single marker, was associated with poorer cognitive ability. 22,23 Taken together, these findings suggest that SVD burden is a risk factor for poststroke cognitive dysfunction.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…better than a single acute infarct or SVD marker at 3 to 6 months after ischemic stroke. 10 Similar observations were made in cross-sectional, population-based studies of older adults, in which the concurrence of multiple SVD markers, compared with a single marker, was associated with poorer cognitive ability. 22,23 Taken together, these findings suggest that SVD burden is a risk factor for poststroke cognitive dysfunction.…”
Section: Discussionsupporting
confidence: 67%
“…9 A recent cross-sectional study reported that a combination of lacunes, WMHs, and perivascular spaces, modeled with a machine learning tool, was a better predictor of cognitive performance at 3 to 6 months after stroke than the stroke lesion itself or one SVD marker. 10 In contrast, the (Tel-Aviv Brain Acute Stroke Cohort) TABASCO study demonstrated that a combination of all SVD markers did not significantly predict cognitive performance at 1 year after stroke or transient ischemic attack (TIA). 11 The above studies either recruited diagnostically mixed populations, 8,9,11 had cross-sectional designs, 8,10 failed to use all 4 SVD markers, 10 or lacked information on cognitive changes.…”
Section: Introductionmentioning
confidence: 98%
“…25 Another study has also reported that a combination of SVD features contributed more to cognitive performance after stroke than the individual measures. 26 These studies have been limited by relatively small sample sizes and brief cognitive measures. Hippocampal volume has not been included in the measures of global SVD burden before.…”
Section: Discussionmentioning
confidence: 99%
“…All participants underwent T2, T1 turbo field echo, fluid-attenuated inversion recovery (FLAIR) imaging using a 3.0-T MRI scanner (Philips 3.0T Achieva; Philips Healthcare, Andover, MA). Subcortical WMHs were defined according to the study of Mok [13]. A lacune was defined as a round or ovoid lesion ≥3 mm and ≤15 mm in diameter found on T1-weighted and T2-weighted images with a perilesional halo on FLAIR images as defined by Wardlaw et al [14].…”
Section: Methodsmentioning
confidence: 99%